Предмет: Алгебра,
автор: muqaddamatakulova1
(1-4/27×(-3)²)³=
![(1 - \frac{4}{27} \times ( - 3) {}^{2} ) {} {}^{3} (1 - \frac{4}{27} \times ( - 3) {}^{2} ) {} {}^{3}](https://tex.z-dn.net/?f=%281+-++%5Cfrac%7B4%7D%7B27%7D+++%5Ctimes+%28+-+3%29+%7B%7D%5E%7B2%7D+%29+%7B%7D+%7B%7D%5E%7B3%7D+)
Ответы
Автор ответа:
0
(1 - 4/27 * (-3)²)³ = (1 - 4/27 * 9)³ = (1 - 4/3)³ = (-1/3)³ = -1/27
Автор ответа:
0
Объяснение:
(1 - 4/27 * (-3)²)³ = (1 - 4/27 * 9)³ = (1 - 4/3 * 1)³ =
(1 - 4/3)³ = (1 - 1 1/3)³ = (-1/3)³ = -1/27
Похожие вопросы